2021
DOI: 10.1007/s12928-021-00777-4
|View full text |Cite
|
Sign up to set email alerts
|

A serial optical frequency-domain imaging study of early and late vascular responses to bioresorbable-polymer sirolimus-eluting stents for the treatment of acute myocardial infarction and stable coronary artery disease patients: results of the MECHANISM-ULTIMASTER study

Abstract: The purpose of this study was to assess early and late vascular healing in response to bioresorbable-polymer sirolimus-eluting stents (BP-SESs) for the treatment of patients with ST-elevation myocardial infarction (STEMI) and stable coronary artery disease (CAD). A total of 106 patients with STEMI and 101 patients with stable-CAD were enrolled. Optical frequency-domain images were acquired at baseline, at 1- or 3-month follow-up, and at 12-month follow-up. In the STEMI and CAD cohorts, the percentage of uncove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Our data demonstrated that the strut coverage of UPF-SES in ACS patients was comparable to that of FRIENDLY OCT trial (98.4% vs. 96.89%, respectively) even though our study population had higher risk of delayed healing than the population of FRIENDLY OCT trial. Moreover, the comparison of the 3 month follow-up OCT findings in patients with ACS among the present study and several previously reported studies was shown in the Supplementary Table 1 [ 15 17 ]. The percentage of covered struts and malapposed struts in UPF-SES were comparable as compared to those of other recent DESs [ 15 17 ].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Our data demonstrated that the strut coverage of UPF-SES in ACS patients was comparable to that of FRIENDLY OCT trial (98.4% vs. 96.89%, respectively) even though our study population had higher risk of delayed healing than the population of FRIENDLY OCT trial. Moreover, the comparison of the 3 month follow-up OCT findings in patients with ACS among the present study and several previously reported studies was shown in the Supplementary Table 1 [ 15 17 ]. The percentage of covered struts and malapposed struts in UPF-SES were comparable as compared to those of other recent DESs [ 15 17 ].…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, the comparison of the 3 month follow-up OCT findings in patients with ACS among the present study and several previously reported studies was shown in the Supplementary Table 1 [ 15 17 ]. The percentage of covered struts and malapposed struts in UPF-SES were comparable as compared to those of other recent DESs [ 15 17 ]. Of course, our sample size were very small and the patient population in the current study was completely different compared to the other studies mentioned above.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The long-term safety of Ultimaster was confirmed by the low rate of late in-stent thrombosis. These favorable antithrombotic properties of the scaffold have been demonstrated in the in vitro models [ 19 ] and are associated with an accelerated tissue coverage and scaffold apposition [ 3 , 20 ] leading to improved vessel healing. Noteworthy, the presence of the “class effect” for all bioresorbable polymer stents is very likely [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol and main results of the MECHANISM-elective study have been reported in detail. 3 All culprit lesions were treated with either one or two Ultimaster BP-SES in standard fashion. The endpoint was the presence of CE at either 1 or 3, and 12 months of the follow-up period.…”
Section: Methodsmentioning
confidence: 99%